CONFLICT MANAGEMENT IN IMPROVING TEAM PERFORMANCE AND IMPROVING TEAM SKILLS IN THE COMPANY PT. STARINDO WORKS SENTOSA: PENGELOLAAN KONFLIK DALAM MENINGKATKAN KINERJA TIM SERTA MENINGKATKAN KETERAMPILAN TIM DI PERUSAHAAN PT. STARINDO KARYA SENTOSA - Yenisa, Yenisa (LPPM UPMI, 2024)
Workplace conflicts can damage team skills, productivity, and employee retention, so it's important to resolve them as quickly as possible. This article explores conflict management strategies that companies like PT Starindo can use to improve team performance. These strategies include encouraging open communication, providing conflict training, encouraging a positive work culture, providing tools and resources, and encouraging problem-solving skills. By implementing these strategies, PT Starindo can improve their team's skills, increase productivity, and stay ahead in a competitive market.